2011
DOI: 10.1016/j.diabres.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and sleep: A complex cause-and-effect relationship

Abstract: Strong associations of diabetes with sleep impairment have been frequently reported. In the present review, we discuss current evidence and hypotheses for how type 1 and type 2 diabetes mellitus are associated with sleep impairment. This association may be described as a vicious circle, where sleep disorders favor the development of type 2 diabetes or exacerbate the metabolic control of both types of diabetes, whereas diabetes itself, especially when associated with poor metabolic control, is often followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
133
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(145 citation statements)
references
References 74 publications
4
133
1
7
Order By: Relevance
“…For some time it has been appreciated that those suffering from metabolic disease, including obesity, impaired glucose tolerance or diabetes also display comorbid sleep difficulties [82]. Most common among these conditions is sleep-disordered breathing, including obstructive sleep apnoea [83].…”
Section: Metabolic Disease and Sleepmentioning
confidence: 99%
“…For some time it has been appreciated that those suffering from metabolic disease, including obesity, impaired glucose tolerance or diabetes also display comorbid sleep difficulties [82]. Most common among these conditions is sleep-disordered breathing, including obstructive sleep apnoea [83].…”
Section: Metabolic Disease and Sleepmentioning
confidence: 99%
“…Poor sleep quality has been linked to several health problems such as cardiovascular disease (5,6), obesity (7), diabetes (8), depression and anxiety (9)(10)(11), and is a risk factor for mortality (12)(13)(14). Previous research has shown that (chronic) stress is an important antecedent of poor sleep quality and that work can be an important cause of stress (15).…”
mentioning
confidence: 99%
“…Cunha, Zanetti and Hass (2008), in one of the scarce studies that assessed sleep in Type 2 Diabetes, analyzed 50 patients, 76% women, 52% married, with ages between 44-79 years, and through the PSQI concluded that the majority (52%) had a poor sleep quality (score ≥5). Likewise, Knutson et al (2006) assessed 161 subjects and Vigg (2003) assessed 220 subjects, both with patients with Type 2 Diabetes, concluded that 71% presented a PSQI score ≥5, showing that Type 2 Diabetes is associated with sleeping problems (Barone & Menna-Barreto, 2011). Rajendran et al (Rajendran, Parthsarathy, Tamilselvan, Seshadri, & Shuaib, 2012) evaluated 120 patients with Type 2 Diabetes (55 women), with a mean age of 53.9 years (SD=9.20) and concluded that the average length of Diabetes diagnosis (7.41±5.90) was positively correlated with the total PSQI score (r=0.181; p<0.050), suggesting that Diabetes duration has a strong influence on patient's sleep (the data was independent of variables as age, gender, body mass index or meds).…”
Section: Discussionmentioning
confidence: 99%